2021
DOI: 10.1002/csc2.20411
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of end‐use quality traits in wheat

Abstract: Wheat (Triticum aestivum L.) is a major cereal food crop in the world. End‐use quality improvement is a major objective in wheat breeding programs. ‘Tiger’ is a hard white winter wheat cultivar with excellent bread baking qualities. The objective of this study was to identify the genetic loci underlying the quality traits in Tiger. A doubled‐haploid (DH) population derived from a cross between Tiger and ‘Danby’ was grown in two environments. A total of 17 quality traits together with grain yield (GY) and strip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 72 publications
(214 reference statements)
2
20
0
Order By: Relevance
“…For instance, S2B_154846350, associated with SKCS size in this study, was located at 4-5 Mb from IWB30179 [2] and QKd.cob-1A (~ 134 Mb, [14]) that were associated with SKCS size and kernel diameter, respectively. Similarly, S2D_563799166 and S5A_578074731 were close to previously identi ed kernel diameter QTL, QKd.hwwgr-2DL (~ 552 Mb, [10]) and QKD.ksu-5A1 (568 Mb, [21]), respectively. For SKCS weight, S2D_563799166 identi ed in this study was positioned at ~12 Mb from QSkw.hwwgr-2DL (552 Mb, [10]) (Supplementary Table S6).…”
Section: Marker-trait Associationssupporting
confidence: 81%
See 4 more Smart Citations
“…For instance, S2B_154846350, associated with SKCS size in this study, was located at 4-5 Mb from IWB30179 [2] and QKd.cob-1A (~ 134 Mb, [14]) that were associated with SKCS size and kernel diameter, respectively. Similarly, S2D_563799166 and S5A_578074731 were close to previously identi ed kernel diameter QTL, QKd.hwwgr-2DL (~ 552 Mb, [10]) and QKD.ksu-5A1 (568 Mb, [21]), respectively. For SKCS weight, S2D_563799166 identi ed in this study was positioned at ~12 Mb from QSkw.hwwgr-2DL (552 Mb, [10]) (Supplementary Table S6).…”
Section: Marker-trait Associationssupporting
confidence: 81%
“…For instance, SKCS hardness associated markers in this study, S1A_583894689, S3A_690786387, S3B_718850970, S5A_480515221, S6B_130163859, S6B_705613777, and S7A_12011069 were located close to the positions of previously reported grain hardness associated markers/QTL, QGh.caas-1A (~575 Mb, [9]), wPt-4725 (709 Mb, [12]), QKh.WJ-3B.3 (~695 Mb, [8]), S5A_463766631 (464 Mb, [22]), IWB11485 (121 Mb, [2]), S6B_703822990 (704 Mb, [22]), wPt-0744 (0.2 Mb, [12]), respectively. Similarly, S1B_635869100 was positioned 8-13 Mb from Qgh-1B [13], QKh.WY-1B.1b [8], QGh.cass-1B [7], QNhi.hwwgr-1BL [10], and QKH.ksw-1B [21]. On chromosome 5B, S5B_549556474 identi ed in this study was found close to Qshi.hwwgr-5BL (566-571 Mb, [10]) and a QTL anked by the SSR marker wmc289 (556 Mb, [11]).…”
Section: Marker-trait Associationsmentioning
confidence: 68%
See 3 more Smart Citations